Use of zinc deposited in deciduous teeth as a retrospective measurement of dietary zinc exposure during early development - N. A. Wahono; L. A. Wakeling; W. Dirks; D. A. Banks; T. J. Shepherd; D. Ford; R. A. Valentine (Frontiers in Oral Health, 2023)
PurposeWe proposed that zinc (Zn) deposition in deciduous teeth would be a timed record of exposure to this essential micronutrient over very early life. We tested this hypothesis by gathering information on the maternal and child's diet during pregnancy and early infancy and measuring mineral deposition in the dentine at points during deciduous tooth development.MethodsWe developed a short food frequency questionnaire (S-FFQ) to record consumption of food containing Zn during pregnancy and over the first year of life of the child in an Indonesian population. Zn, Sr and Ca were measured by laser ablation ICP-MS in a series of points across the developmental timeline in deciduous teeth extracted from 18 children undergoing the process as part of dental treatment whose mothers completed the SFFQ. Mothers and children were classified into either high Zn or low Zn groups according to calculated daily Zn intake.ResultsThe Zn/Sr ratio in dentine deposited over late pregnancy and 0–3 months post-partum was higher (p < 0.001, 2-way ANOVA; p < 0.05 by Holm-Sidak post hoc test) in the teeth of children of mothers classified as high Zn consumers (n = 10) than in children of mothers classified as low Zn consumers (n = 8).ConclusionThe S-FFQ was validated internally as adequately accurate to measure zinc intake retrospectively during pregnancy and post-partum (∼7 years prior) by virtue of the correlation with measurements of zinc in deciduous teeth. The ratio of Zn/Sr in deciduous teeth appears to be a biomarker of exposure to zinc nutrition during early development and offers promise for use as a record of prior exposure along a timeline for research studies and, potentially, to identify individuals at heightened risk of detrimental impacts of poor early life zinc nutrition on health in later life and to implement preventative interventions.